From family rental houses to low-rent houses - the research on urban village renewal based on renting - Luo , Ji; Peng , Yang (2008)

(untitled)
Urban villages are the particular outcome of the China urbanization and now they become the obstructions for the urban development. Many studies have been made concerning the problems in the village and propose some village renewal patterns. However most of them were in a dilemma due to the huge corresponding compensation and villagers’ unwillingness. In this article, after in-depth reviewing the specific phenomenon of renting in the village and taking account of the puzzle of Low-rent housing constructions in today’s China, we propose the Low-rent housing oriented village renewal pattern as the effective way to advance the urban renewal and national Low-rent housing program. Moreover, we argue the viability and dynamic mechanism of this urban renewal pattern, as result we suggest take the “Admittance”, “Cooperation” and “Centralization” as the key points for the implementation of our idea.